A Qualitative Study of Information challenges in the Cloud - George, Elaine; Gao, Jing (ACIS, 2014)
This paper explores the modified information management and information governance challenges faced by organizations when shifting from traditional on-site model to the cloud. The specific cloud information management and governance challenges, often ignored by businesses due to their experience in traditional information governance and outsourcing, have the potential to threaten the sustainability of a business that is new to the cloud. As cloud solutions from powerful vendors are being thrust at unsuspecting customers, it is imperative that organizations understand information related changes required in the cloud to ensure regulatory compliance. A series of qualitative interviews involving expert practitioners has helped investigate the information challenges; and the barriers and drivers of cloud adoption in the current market with some unexpected observations.